The legislation on whistleblowers’ protection in the Slovak Republic - Kanková, Helena; Molnárová, Iveta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to present the content of the legal regulation on the protection of whistleblowers in the Slovak Republic. The purpose of the new legislation was to establish efficient and effective whistleblowers’ protection, the report whereof can contribute or contributed significantly to the clearing up of corruption or other serious antisocial activity and to disclosing or convicting its offender, based on the information that came to his or her knowledge in connection with the execution of his or her employment, profession, position or function. The need to introduce protection of whistleblowers of corruption crime in the legal system of the Slovak Republic ensued from a number of international obligations and recommendations, by which the Slovak Republic is bound. One of them is the Convention on Combating Bribery of Foreign Public Officials in International Business Transactions, adopted by the international organization OECD.
Keywords: corruption crime; serious antisocial activity; protected whistleblower; request for protection in criminal proceedings; internal system for dealing with complaints